Law's Practical Wisdom : the Theory and Practice of Law Making in New Governance Structures in the European Union. - Sideri, Katerina (Ashgate Pub., 2007)
This book presents a theory of law making in the European Union, focusing on new governance structures which promote deliberation, proceduralization, and dialogue. The empirical substantiation of the argument is premised on case studies from the EU, such as the Information Society Directive, domain name dispute resolution by ICANN, Internet filters, and the proposal for a Directive on the patentability of computer-implemented inventions.